Instituições camponesas como Estado? Os conselhos aldeões egípcios (qnbt) do Egito do Reino Novo - Moraes Lima, Fábio Afonso Frizzo de ([Actas])
At the New Kingdom, the pharaonic state expands its exploitation over both the foreign areas and the egyptian peasant community. If we take the state as an form of social organization we could perceive its subsumption over pre-state comunal peasant forms of social organization. In his Prison Notebooks, Antonio Gramsci stated that, in precapitalism, subaltern institutions sometimes performs state functions. This is the case of the egyptian qnbt, an village council which performs state functions today seen as administrative, civil and legal. The study of Deir el-Medina's workers village and its qnbt shows how a villager institution performs state functions, proving the aggressive expansion of the state over the peasant's forms of social organization